A new benzophenone glycoside from the leaves of Mitracarpus villosus. Issue 20 (18th October 2017) - Ngwoke, Kenneth G.; Orame, Njideka; Liu, Shuai; Okoye, Festus B. C.; Daletos, Georgios; Proksch, Peter
Abstract: A new benzophenone glycoside, mitraphenone A (1 ), together with three known compounds (2 –4 ) were isolated from the leaves of the traditionally used medicinal plant Mitracarpus villosus (Rubiaceae) collected in Nigeria. A combination of one- and two-dimensional NMR spectroscopic and mass spectrometric measurements were carried out to identify the structure of1 . All isolated compounds (1 –4 ) were screened for their antibacterial activity against several Gram-positive and Gram-negative bacteria. Compound1 exhibited moderate activity against Enterococcus faecium (strains ATCC 35667 and ATCC 700221) and Staphylococcus aureus ATCC 25923 with MIC values ranging from 25 to 50 μM. Abstract :